THE ROLE OF TEACHING FOUR CAMPUS STUDENTS IN IMPROVING LITERACY AND NUMERACY AT PRIMARY SCHOOL 3 PEJANGGIK - Muhammad Sobri; Umar (El Midad, 2023)
This study aims to explain the role of fourth-generation campus teaching students in improving students' literacy and numeracy at Pejanggik 3 Public Elementary School. This type of research is descriptive qualitative research. The data collection technique uses observation and documentation. The data that has been collected is then analyzed using the Milles and Huberman Model with the following steps: data reduction, data presentation, verification and conclusions. Based on data analysis, the conclusions in this study are 1) there are several programs carried out during assignments by teaching 4 campus students that help improve literacy and numeracy in Pejanggik elementary school, namely: Campus Teaching Classes, Free Hours, Morning Speeches, Literature Workshops, Literacy Corner and reading clinics and Mading (wall magazines); 2) there was an increase in students' literacy skills as indicated by the results of the pre-test with the percentage of students who answered correctly by 30% and at the time of the post-test it increased to 40%. While the numeration is shown in the results of the pre test with the percentage of students who answered correctly by 18% and during the post test it increased to 40%.